2020
DOI: 10.47197/retos.v38i38.78499
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias de género en el perfil y los hábitos de practicantes de actividades en el medio natural (Gender differences in the profile and habits of practitioners of outdoor activities)

Abstract: Los estereotipos de género aún se pueden palpar en el medio natural, pues siguen existiendo determinantes culturales, de tipo sexista, que influyen a la hora de practicar actividades físicas en la naturaleza. El objetivo del presente estudio fue analizar el perfil de los practicantes de actividades en el medio natural, las características y los hábitos de práctica identificando las posibles diferencias de género existentes. La metodología empleada ha consistido en la realización de una encuesta  mediante la di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…Different research supports these results, where resilient athletes who are more satisfied with life predict positively and significantly higher EI [47]. In relation to these aspects, several elements coexist that connect resilience and life satisfaction, such as health, sports performance and context, as well as the emotions experienced in personal activities and relationships [3,[21][22][23], so that athletes who show higher personal competences also show higher life satisfaction, where resilience plays a mediating role with EI [47,73].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Different research supports these results, where resilient athletes who are more satisfied with life predict positively and significantly higher EI [47]. In relation to these aspects, several elements coexist that connect resilience and life satisfaction, such as health, sports performance and context, as well as the emotions experienced in personal activities and relationships [3,[21][22][23], so that athletes who show higher personal competences also show higher life satisfaction, where resilience plays a mediating role with EI [47,73].…”
Section: Discussionmentioning
confidence: 96%
“…Mountain sports have a sporting environment with its own characteristics, different from other sports modalities and risk conditions in some cases, which may affect the profile of athletes physically, but above all psychologically. The pandemic has produced some changes in behaviour and in the ways of participating in sport in the Spanish population [3]; hiking practitioners have grown exponentially, but not all of them are federated [4]. In this regard, we present this study, which takes as participants those people who practise mountain sports and who are linked to the only Spanish sports federation that will participate in the Summer Olympic Games (climbing) and in the Winter Olympic Games through ski mountaineering, which is debuting as an Olympic discipline at Milan-Cortina d'Ampezzo 2026.…”
Section: Introductionmentioning
confidence: 99%
“…This perspective emphasizes the need to understand why some persons do not engage in sufficient physical activity and may not be getting all the physiological and psychological health benefits associated with an active lifestyle (Bermejo, Almagro, & Rebollo, 2017;Blanco, Soto, Benitez, Mondaca, & Jurado, 2019;Casper, Harrolle, & Kelley, 2013). It also underscores the importance of approaches using a multilevel perspective amidst the growing evidence that engagement in physical activity is influenced by the interaction and intersection of individual, societal, and built environment factors (Carlson et al, 2012;Jáuregui et al, 2017;Mitáš et al, 2019;Salvo et al, 2017;Schulz et al, 2013;Talavera & Saldaña, 2020) As described by Henderson and Gibson (2013) in their integrative review, most women are likely to believe that LTPA is right for them, yet many are not able to be physically active on a regular basis. Research examining the role of gender on sport, fitness, exercise and other forms of free-time physical activity has consistently shown that women face more constraints than men on their access to leisure opportunities and resources (Blanco et al, 2019;Evenson, Williamson, Han, McKenzie, & Cohen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…general (Fraguela-Vale et al, 2020;Martín Talavera & Mediavilla Saldaña, 2020;Nuviala Nuviala et al, 2021). Pero en el ámbito de los estudios universitarios vinculados con la actividad física y el deporte, hay pocos trabajos que hayan analizado la presencia de las mujeres y menos aún sobre las características y condicionantes de su acceso.…”
unclassified